Respiratory Entrainment and Reverse Triggering in a Mechanically Ventilated Patient - de Vries, Heder J.; Jonkman, Annemijn H.; Tuinman, Pieter R.; Girbes, Armand R. J.; Heunks, Leo M. A. (Annals of the American Thoracic Society, 2019)
Because the first response to a patient "fighting the ventilator" is often to increase sedation, it is essential to recognize this form of patient-ventilator interaction. [...]reducing sedation and changing respiratory rate, inspiratory pressure, and applied volume can disrupt entrainment and prevent reverse triggering. Unfortunately, these measures were ineffective in our patient. [...]the neuromuscular blocker rocuronium was administered to abolish respiratory muscle output and prevent reverse-triggered efforts with breath stacking. [...]reversetriggered breaths differ minimally in the timing, duration, and magnitude of inspiratory effort, which can be measured and quantified by either diaphragmatic electromyography or esophageal pressure measurements (Figure 3).